The Role of Alarmins in the Pathogenesis of Asthma - Paulina Plewa; Julia Pokwicka; Estera Bakinowska; Kajetan Kiełbowski; Andrzej Pawlik (Biomolecules, 2025)
Asthma is defined as a chronic respiratory disease, the processes of which are mainly related to the hyperreactivity of the immune system. Airway hyperresponsiveness and remodeling are other hallmarks of asthma that are strongly involved in the progression of the disease. Moreover, asthma is associated with the occurrence of atopic dermatitis, chronic sinusitis, allergic rhinitis, and a high profile of T2-type cytokines, such as IL-4, IL-5 and IL-13. The hyperresponsiveness of the immune system is a consequence of aberrant levels of alarmins, endogenous molecules that induce pro-inflammatory responses. They are released as a result of a defect or cell death, leading to the initiation of an inflammatory reaction. High-mobility group box 1 (HMGB1), S100 proteins, interleukin-33 (IL-33), thymic stromal lymphopoietin (TSLP), and IL-25 bind to various receptors, influencing the behavior of immune cells, resulting in stimulated migration and activation of these cells. In this review, we will discuss the potential role of alarmins in the pathogenesis of asthma.